Enteral Feeding Practices for Very Preterm and Very Low Birth Weight Infants in Nigeria and Kenya - Tongo, Olukemi O.; Olwala, Macrine A.; Talbert, Alison W.; Nabwera, Helen M.; Akindolire, Abimbola E.; Otieno, Walter; Nalwa, Grace M.; Andang'o, Pauline E. A.; Mwangome, Martha K.; Abdulkadir, Isa; Ezeaka, Chinyere V.; Ezenwa, Beatrice N.; et al. (Frontiers in Pediatrics, 2022)
Background: Optimizing nutrition in very preterm (28 - 32 weeks gestation) and very low birth weight (VLBW; 1000g to <1500g) infants has potential to improve their survival, growth, and long-term health outcomes. Aim: To assess feeding practices in Nigeria and Kenya for hospitalized very preterm and VLBW newborn infants. Methods: This was a cross-sectional study using convenience sampling. A standard questionnaire was sent to doctors working in neonatal units in Nigeria and Kenya. Results: Of 50 respondents, 37 (74.0%) were from Nigeria and 13 (26.0%) from Kenya. All initiated enteral feeds with breastmilk, with 24 (48.0%) initiating within 24 hours. Only 28 (56.0%) used written feeding guidelines. Starting volumes ranged between 10 – 80 ml/kg/day. Median volume advancement of feeds was 20 ml/kg/day (IQR 10 – 20) with infants reaching full feeds in 8 days (IQR 6 – 12). 26 (52.0%) of the units fed the infants 2 hourly. Breastmilk fortification was practiced in 7 (14.0%) units, while folate, iron, calcium, and phosphorus were prescribed in 42 (84.0%), 36 (72.0%), 22 (44.0%), 5 (10.0%) of these units, respectively. No unit had access to donor breastmilk, and only 18 (36.0%) had storage facilities for expressed breastmilk. Twelve (24.0%) used wet nurses whilst 30 (60.0%) used formula feeds. Conclusion: Feeding practices for hospitalized very preterm and VLBW infants vary widely within Nigeria and Kenya, likely because of lack of locally generated evidence. High quality research that informs the feeding of these infants in the context of limited human resources, technology, and consumables, is urgently needed.